2019
DOI: 10.1108/ijopm-04-2018-0201
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between investments in lean practices and operational performance

Abstract: CitationOnofrei, G., Prester, J., Fynes, B., Humphreys, P., and Wiengarten, F. (2019) 'The relationship between investments in lean practices and operational performance: Exploring the moderating effects of operational intellectual capital', The relationship between investments in lean practices and operational performance: exploring the moderating effects of operational intellectual capitalAbstract Purpose -Prior research has shown that operational intellectual capital (OIC) and investments in lean practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 92 publications
(196 reference statements)
3
39
1
1
Order By: Relevance
“…Malhotra and Sharma (2008) state that in order to make valid findings and conclusions, it is important that measurement invariance across groups is assessed, to ascertain whether or not measurement items, under varying conditions, yield the same attributes. A number of recent studies confirmed measurement equivalence in the GMRG data set through various tests (e.g., Schoenherr & Narasimhan, 2012; Wiengarten et al, 2018; Onofrei, Prester, Fynes, Humphreys, & Wiengarten, 2019).…”
Section: Analysis and Resultsmentioning
confidence: 89%
“…Malhotra and Sharma (2008) state that in order to make valid findings and conclusions, it is important that measurement invariance across groups is assessed, to ascertain whether or not measurement items, under varying conditions, yield the same attributes. A number of recent studies confirmed measurement equivalence in the GMRG data set through various tests (e.g., Schoenherr & Narasimhan, 2012; Wiengarten et al, 2018; Onofrei, Prester, Fynes, Humphreys, & Wiengarten, 2019).…”
Section: Analysis and Resultsmentioning
confidence: 89%
“…This is particularly important because measuring the extent of lean implementation in a factory is difficult. Most important, unlike many quantitative studies of lean (and other improvement programs) that are based on cross-sectional data from many firms and industries (a few examples include Shah and Ward, 2003; Shah et al , 2008; Fullerton et al , 2014; Jacobs et al , 2015; Onofrei and Prester, 2019), our sample is from one company, and all the factories operate in a narrow segment of one industry. Hence, our analysis implicitly controls for a variety of contextual variables.…”
Section: Research Setting and Methodsmentioning
confidence: 99%
“…As another reliability check, following the general consensus in the literature that a factory's operational performance improves as it implements lean more extensively (e.g. Shah and Ward, 2003; Browning and Heath, 2009; Fullerton et al , 2014; Netland and Ferdows, 2016; Onofrei and Prester, 2019), we reviewed internal company factory performance data to see if there were any anomalies; we found none. Overall, we believe GEM's Lean Implementation assessment scores are reliable measures to gauge the extent of lean implementation in a factory.…”
Section: Research Setting and Methodsmentioning
confidence: 99%
“…[8]; Nuñez I., Prieto M. [9]; Trelová S., Olšavský F. [10], Onofrei G. и др. [11] и других) сформулирован ряд подходов, выводы которых нельзя обозначить как согласующиеся, образующие солидарно видимую методическую платформу планирования инвестиций в человеческий капитал обрабатывающей промышленности. Общими недостатками подходов к осмыслению проблематики автор видит:…”
Section: актуальность и проблематика исследованияunclassified